Membangun Kesejahteraan melalui Pembangkit Listrik Tenaga Mikro Hidro Berbasis Masyarakat di Desa Baturotok, Kabupaten Sumbawa - Dwipayana, I Kadek Dede; Mareta, Josefhin; Reksa, Abdul Fikri Angga (Masyarakat Indonesia, 2023)
Despite claims of increasing electrification ratios, some regions in Indonesia still need access to PLN electricity, such as Baturotok Village, located in Batulanteh Subdistrict, Sumbawa Regency. Nevertheless, the community has endeavored to establish self-sustained lighting sources through Community-Based Micro-Hydro Power Plants (PLTMH). This article discusses the collaborative actions and community participation in building PLTMH. Additionally, this article explores the challenges and sustainability aspects of this green infrastructure. The research shows that the community benefits from the presence of PLTMH. Amidst the limitations in electricity, the Baturotok villagers enhance their knowledge and strengthen their socio-cultural networks. That encourages active and consistent participation from the community in the construction and maintenance of PLTMH. However, the coverage of PLTMH has yet to reach all residents of Baturotok Village. Thus, the anticipated improvement in welfare is not significantly visible. Future initiatives should focus on infrastructure development and enhancing the Human Resources of the Baturotok community.